The Influence of Brand Image and Product Price towards Purchase Decision at E-commerce Tokopedia - Adhi Prasetio; Adevia Puji Angelina (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
Internet growth in Indonesia has rapidly affected economic stability. Buying and selling transaction becoming more efficient and could be done without face to face through online platform such as e-commerce as the effect of internet development. Tokopedia is one of the successful e-commerce which was ranked in the first position of the highest transaction in Indonesia, therefore this research for a benchmark is needed. The purpose of this study was to determine partially the influence of brand image and product price towards purchase decision and the influence of simultaneous brand image and product price towards purchase decision. This research was conducted on e-commerce Tokopedia users with sample around 400 taken using purposive sampling. Data was collected using online questionnaire with multiple linear regression technique analysis. Data was proceed using SPSS 25 for Mac. The result show brand image and product price have a partially significant effect towards on Tokopedia e-commerce purchase decision, brand image and product price have a simultaneous significant effect towards on Tokopedia e-commerce purchase decision.